Use and acceptance of complementary and alternative medicine among medical students: a cross sectional study from Palestine - Ahmad M. Samara; Ethar R. Barabra; Hala N. Quzaih; Sa'ed H. Zyoud (BMC, 2019)
Abstract Background Teaching Complementary and alternative medicine (CAM) in medical schools is becoming prevalent worldwide. Few studies have been conducted to evaluate medical students' knowledge and attitude toward CAM. Therefore, this study was designed to assess CAM knowledge, attitudes, and beliefs among Palestinian medical students. Methods This study was developed in a cross-sectional design. It targeted medical students at An-Najah National University, between January and April of 2018. We gathered the data from students using a questionnaire printed as a hard copy. Medical students of both sexes in their 4th, 5th, or 6th year of studies were included in the survey. The questionnaire consisted of 3 sections: demographic characteristics and detailed practices of the participants, their attitude and held beliefs towards CAM, and their knowledge on CAM. Mann-Whitney U Test and Kruskal-Wallis Test were used to test if there were differences between knowledge about CAM and the characteristics of the participants. Results Of the 300 medical students who were offered the questionnaire, 251 students (43.8% male and 56.2% female) were included in the final analysis. Out of a maximum of 8 points, the mean knowledge score of the participants was 2.0 ± 1.6. The Kruskal-Wallis test showed a statistically significant difference in overall knowledge score among students of different year groups, with students at lower levels obtaining higher scores (P < 0.001). Additionally, the highest knowledge scores were found in students with low income, and students who came from the Palestinian refugee camps (P < 0.001). Students frequently recommended CAM modalities, with herbal medicine being the most recognized and used CAM modality and Ayurvedic medicine being the least recognized and recommended one. Social media was the most popular source of information about CAM, cited by 72.9% of the participants. Participants generally had a good attitude towards CAM but held varying beliefs about it. Conclusions In the current study, a knowledge gap regarding CAM was found among medical students in our sample, despite their good attitude towards the subject. Also, there was a general acceptance to include materials on CAM within the curriculum of medical students.